Evaluation of Vertebroplasty with a Validated Outcome Measure: The Roland-Morris Disability Questionnaire - Trout, Andrew T.; Kallmes, David F.; Gray, Leigh A.; Goodnature, Barbara A.; Everson, Sandra L.; Comstock, Bryan A.; Jarvik, Jeffrey G. (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Vertebroplasty is rapidly disseminating as a treatment for vertebral compression fractures, but its efficacy has not been assessed with a well-validated, back pain–specific instrument. We report the use of the Roland-Morris Disability Questionnaire (RDQ) in patients undergoing vertebroplasty for painful osteoporotic compression fractures.METHODS: Retrospective review of patients treated with vertebroplasty who completed the RDQ and 2 verbal pain scales (0–10) for pain at rest and pain with activity at baseline, 1 week, 1 month, 6 months, and 1 year post-vertebroplasty. Changes in outcome measures were analyzed by using a paired t test and correlations were assessed with Spearman ρ. Multiple linear regression was used to analyze the relationship between baseline scores and independent variables.RESULTS: One hundred thirteen patients were treated at 164 vertebral levels. At baseline, RDQ scores were associated with rest and activity pain (P < .001 and P = .002, respectively) but were not associated with other independent variables. All 3 outcome scores decreased by 1 week and remained improved through maximal follow-up (P < .001). RDQ scores improved by a mean of 7.0 points at 1 week and remained improved at 1 year (P = .02). RDQ scores correlated with both rest and activity pain, but the absolute correlation was slightly better (+0.15 on average) with activity pain.CONCLUSIONS: Patients who underwent vertebroplasty experienced relief of back pain and symptoms, as shown by improvement in verbal pain and RDQ scores. The RDQ correlates well with measures of pain, shows clinically significant improvement and is responsive to changes across time. More important, the RDQ provides an easily administered, well-validated, back pain–specific outcome measure that could be adopted to assess vertebroplasty outcomes.